Protease-Activated Receptors and other G-Protein-Coupled Receptors: the Melanoma Connection - Rosero, Rebecca A.; Villares, Gabriel J.; Bar-Eli, Menashe (Frontiers in Genetics, 2016)
The vast array of G-protein-coupled receptors (GPCRs) play crucial roles in both physiological and pathological processes, including vision, coagulation, inflammation, autophagy, and cell proliferation. GPCRs also affect processes that augment cell proliferation and metastases in many cancers including melanoma. Melanoma is the deadliest form of skin cancer, yet limited therapeutic modalities are available to patients with metastatic melanoma. Studies have found that both chemokine receptors and protease-activated receptors, both of which are GPCRs, are central to the metastatic melanoma phenotype and may serve as potential targets in novel therapies against melanoma and other cancers.